2012
DOI: 10.1111/j.1365-2125.2012.04336.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manidipine vs. amlodipine on intrarenal haemodynamics in patients with arterial hypertension

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Dihydropyridine calcium channel blockers (CCBs) are widely used antihypertensive drugs. Evidence from animal studies indicates there are differences between CCBs in their renal haemodynamic effects suggesting that manidipine reduces, whereas amlodipine increases intraglomerular pressure but data from humans are scarce. WHAT THIS STUDY ADDS• In this study amlodipine was found to increase significantly intraglomerular pressure whereas manidipine decreased intraglomerular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
(32 reference statements)
0
15
0
2
Order By: Relevance
“…On the other hand, another finding in this study was that treatment with CCBs was associated with albuminuria. A recent study has demonstrated that the CCB, amlodipine, increased albuminuria by decreasing the resistance of the afferent arteriole in the glomerulus, leading to increased intraglomerular pressure . Even though the CCB used among the participants in this study was predominantly nifedipine, the mechanism that explains the association with albuminuria may be similar.…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, another finding in this study was that treatment with CCBs was associated with albuminuria. A recent study has demonstrated that the CCB, amlodipine, increased albuminuria by decreasing the resistance of the afferent arteriole in the glomerulus, leading to increased intraglomerular pressure . Even though the CCB used among the participants in this study was predominantly nifedipine, the mechanism that explains the association with albuminuria may be similar.…”
Section: Discussionmentioning
confidence: 60%
“…Indirect intraglomerular haemodynamic parameters were estimated using equations derived by Gomez based on data from animal studies . These equations were successfully used in a similar manner to evaluate patients with conditions such as hypertension, endocrine disorders and Type 1 diabetes . Assumptions imposed by Gomez's equations were the following: (1) intrarenal vascular resistances are divided into afferent, post‐glomerular and efferent; (2) hydrostatic pressures within the renal tubules, venules, Bowman's space and interstitium ( P Bow ) are in equilibrium of 10 mmHg; (3) glomerulus is in filtration disequilibrium; and (4) the gross filtration coefficient ( K FG ) is 0.0867 ml/s/mmHg given a normal kidney physiology (GFR = 130 ml/min, oncotic pressure π G is 25 mmHg and P GLO = 60 mmHg, given Winton's indirect estimates in dogs that glomerular pressure is roughly two‐thirds of the mean arterial pressure (MAP) ).…”
Section: Methodsmentioning
confidence: 99%
“…Instead we utilized the model developed by Gomez [21] and later adapted by other research groups [28][29][30]. The reliability of the estimates rests on several assumptions as outlined in previous studies [29,31,32], and the most consistent results are probably achieved in individuals with two functionally normal and similar kidneys as it likely applies to the DHyPP cohort. In accordance with previous findings, we found that angiotensin II blockade selectively reduces R A without affecting P glom or R E [31].…”
Section: Long-term Blood Pressure Changesmentioning
confidence: 99%